AB0894 Treatment adherence to urate-lowering therapy in chinese gout patients. (15th June 2017) - Yin, R; Cao, H; Fu, T; Zhang, Q; Zhang, L; Li, L; Gu, Z
Abstract : Background: Gout, which is characterised by deposition of monosodium urate monohydrate (MSU) in synovial fluid and other tissues, is the most common form of inflammatory arthritis in man and older women. In addition to recurrent acute arthritis, subcutaneous tophi and chronic painful arthritis, gout also affects morbidity and premature mortality. Previous studies have reported that effective ULT can decrease sUA levels enough to prevent further crystal formation, dissolve existing urate crystals and eliminate the causative agent, thus reducing the frequency of acute gout attacks and preventing urate nephropathy, uric acid nephrolithiasis, and the deposition of tophi: a common cause of progressive joint damage, deformity and functional impairment, making gout the only chronic arthritis that can be "cured". However, gout patents' adherence rate to ULT is low, ranged from 10 to 46%. Emerging data suggest that poor adherence to long-term ULT use may be an important contributor to the suboptimal outcomes seen in gout and nonadherence may be worse in gout than in any other chronic disease. This suggests that there is a strong need to make a further study on drug adherence and its risk factors. Objectives: Non-adherence in gout patients using urate-lowering therapy (ULT) may lead to joint destruction and permanent disability. Purpose of this cross-section survey was to explore Chinese gout patients' adherence rates and investigate potential risk factors for medication non-adherence. Methods: A total of 129 gout patients were recruited from the Affiliated Hospital of Nantong University from August 2015 to September 2016. Patients were asked to complete a standardized self-report questionnaires (Compliance Questionnaire on Rheumatology, Treatment Satisfaction Questionnaire for Medication version II, Health Assessment Questionnaire, Confidence in gout treatment questionnaire, Gout Knowledge Questionnaire, Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, and 36-Item Short Form Health Survey). Data was analyzed by independent sample t-test, rank sum test, chi-square analysis as well as logistic regression modeling. Results: Based on CQR, 9.6% of gout patients were adherent to ULT. Adherence was associated with HAQ, GKQ, treatment satisfaction for medication, confidence in gout treatment and MCS. Other demographic, clinical and psychological characteristics were not related to adherence. Logistic regression models identified HAQ, GKQ and MCS as predictors of medication non-adherence. Conclusions: In the current study, 90.4% of gout patients didn't adhere to their ULT prescription. HAQ, GKQ, treatment satisfaction for medication, confidence in gout treatment and MCS were relevant to medication adherence, and HAQ, GKQ and MCS were independent predictors of medication non-adherence in patients with gout. These findings could help medical personnel develop useful interventions to improve gout patients' medication adherence and quality of life. Acknowledgements: This study was supported by grants from the Cultivative Distinguished Young Scholars Project of Nantong University (2nd); the 2015 Graduate Innovation Project of Nantong University (YKC15075); and College graduate research and innovation of Jiangsu Province (KYZZ15–0353). Disclosure of Interest: None declared